2000
DOI: 10.1161/01.hyp.35.3.746
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol Normalizes Endothelial Dysfunction in Type 2 Diabetics With Mild Hypertension

Abstract: Abstract-Therapeutic strategies against free radicals have mostly focused on the augmentation of antioxidant defenses (eg, vitamins C and E). A novel approach is to prevent free radical generation by the enzyme system xanthine oxidase. We examined whether the inhibition of xanthine oxidase with allopurinol can improve endothelial function in subjects with type 2 diabetes and coexisting mild hypertension compared with control subjects of a similar age. We examined 23 subjects (11 patients with type 2 diabetes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
308
0
9

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 425 publications
(329 citation statements)
references
References 40 publications
12
308
0
9
Order By: Relevance
“…Allopurinol is an established drug to inhibit the activity of this enzyme and is commonly used to block the production of uric acid. The drug has been shown to reduce the OS in DMT-2 patients (15,50,73,74). Experimental studies have also corroborated these findings.…”
Section: Xanthine Oxidasementioning
confidence: 72%
See 1 more Smart Citation
“…Allopurinol is an established drug to inhibit the activity of this enzyme and is commonly used to block the production of uric acid. The drug has been shown to reduce the OS in DMT-2 patients (15,50,73,74). Experimental studies have also corroborated these findings.…”
Section: Xanthine Oxidasementioning
confidence: 72%
“…Experimental studies have also corroborated these findings. Some workers (74) have proposed that over expression of xanthine oxidase is a major contributor in DMT-2 but significant contribution of this enzyme in the raised OS in DMT-2 or diabetic complications is questionable.…”
Section: Xanthine Oxidasementioning
confidence: 99%
“…46 Allopurinol, can reverse the impaired endothelial NO production in both heart failure and type 2 diabetes. 47,48 Although allopurinol leads to significant UA reductions most investigators believe that its beneficial effect may be by reducing oxidative stress. It is possible that treating hyperuricaemia may be effective in lowering BP when hyperuricaemia has not been present for a long time (such as in children with HT and in patients given short-term treatment with cyclosporine or diuretics) or when subjects are given a lowsalt diet which would remove the renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…[57][58][59][60] Although the mechanism by which uric acid exerts its pathogenetic effect on cardiovascular and cerebrovascular complications is still unclear, high uric acid levels have been shown to induce inflammation, endothelial dysfunction, oxidative metabolism, and platelet adhesion and aggregation. [61][62][63][64][65] All these changes induced by high uric acid levels could conceivably lead to cardiovascular complications and stroke and therefore, drugs that lower uric acid levels have been shown to reverse these changes. [61][62][63][64][65] Losartan, in exception to other ARBs, lowers uric acid levels and its use for the treatment of hypertension has been shown to decrease the incidence of cardiovascular complications and strokes.…”
Section: Aii-mediated Effects Of Arbsmentioning
confidence: 99%
“…[61][62][63][64][65] All these changes induced by high uric acid levels could conceivably lead to cardiovascular complications and stroke and therefore, drugs that lower uric acid levels have been shown to reverse these changes. [61][62][63][64][65] Losartan, in exception to other ARBs, lowers uric acid levels and its use for the treatment of hypertension has been shown to decrease the incidence of cardiovascular complications and strokes. 66,67 In fact, the results from the LIFE study showed that the baseline uric acid level was significantly associated with cardiovascular complications and strokes, especially in women, and that its lowering with losartan accounted for 29% of the reduction of strokes compared to atenolol.…”
Section: Aii-mediated Effects Of Arbsmentioning
confidence: 99%